Development of Maze Puzzle Learning Media in Indonesian Language Learning Storytelling Material - Marvika, Billyana; Lian, Bukman; Selegi, Susanti Faipri (Journal of Social Work and Science Education, 2023)
This study aims to produce valid and appropriate Indonesian language learning media material for storytelling fiction and non-fiction. The type of research being developed is Research and Development (R&D) referring to the 4D model, namely Define, Design, Development, and Disseminate. This research produced a product in the form of a maze puzzle with a size of 70 cm × 60 cm with wood or plywood as the basic material. Data analysis techniques were carried out using percentage calculations which were then described to obtain valid and feasible media results. Based on the results of data analysis using media validation, a percentage of 82% was obtained with very valid criteria, and for material expert results, a percentage of 80% was obtained with valid criteria, then the results of the student response questionnaire from one to one results obtained an average value of 90.8% with the criteria very feasible, then the small group questionnaire results obtained an average score of 90.2% with very feasible criteria and the field test obtained an average value of 94.64% with very feasible criteria. It can be seen from the group of criteria included in the criteria 81% - 100% with a very decent category. Thus, it can be concluded that the maze puzzle media in Indonesian language learning storytelling material can be said to be valid and feasible.